Designing Intelligent Nanomaterials to Achieve Highly Sensitive Diagnoses and Multimodality Therapy of Bladder Cancer. Issue 2 (4th January 2023) - Li, Guanlin; Wu, Sicheng; Chen, Wenzhe; Duan, Xiaolu; Sun, Xinyuan; Li, Shujue; Mai, Zanlin; Wu, Wenzheng; Zeng, Guohua; Liu, Hongxing; Chen, Tianfeng
Abstract: Bladder cancer (BC) is among the most common malignant tumors of the genitourinary system worldwide. In recent years, the rate of BC incidence has increased, and the recurrence rate is high, resulting in poor quality of life for patients. Therefore, how to develop an effective method to achieve synchronous precise diagnoses and BC therapies is a difficult problem to solve clinically. Previous reports usually focus on the role of nanomaterials as drug delivery carriers, while a summary of the functional design and application of nanomaterials is lacking. Summarizing the application of functional nanomaterials in high‐sensitivity diagnosis and multimodality therapy of BC is urgently needed. This review summarizes the application of nanotechnology in BC diagnosis, including the application of nanotechnology in the sensoring of BC biomarkers and their role in monitoring BC. In addition, conventional and combination therapies strategy in potential BC therapy are analyzed. Moreover, different kinds of nanomaterials in BC multimodal therapy according to pathological features of BC are also outlined. The goal of this review is to present an overview of the application of nanomaterials in the theranostics of BC to provide guidance for the application of functional nanomaterials to precisely diagnose and treat BC. Abstract : Bladder cancer (BC) is the most common malignant tumors of the genitourinary system worldwide. This review summarizes the application of nanotechnology in BC diagnosis and their potential applications in BC therapy regarding increasing drug retention and adhesion, enhancing drug penetration, overcoming drug resistance, and improving drug targeting. This review presents an overview of the application of nanomaterials in the BC theranostics.